(untitled) (Faculty of Education Scientific Journal, 2025)
This Abstract: In this present, we extend the notion of neighborhoods in families of analytic functions using q-derivative . A systematic study of inclusion relationships among (m, δ, q)-neighborhoods of canonically normalized analytic functions with negative coefficients is presented